(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article reflects on the assessment given to linguopoetics and different approaches to this phenomenon through the analysis of poems by Uzbek and world poets as a branch of linguistics. The linguistic analysis of artistic poetry is devoted to giving through examples and stable combinations and explaining the essence of this linguistic concept.